Mindfulness training in medical education as a means to improve resilience, empathy, and mental health in the medical profession - Vidal, Edison Iglesias de Oliveira [UNESP]; Ribeiro, Luiz Fernando Alvarenga; Carvalho-Filho, Marco Antonio de; Fukushima, Fernanda Bono [UNESP] (Baishideng Publishing Group Inc, 2024)
The high rates of depression, burnout, and increased risk of suicide among medical students, residents, and physicians in comparison with other careers signal a mental health crisis within our profession. We contend that this crisis coupled with the inadequate acquisition of interpersonal skills during medical education results from the interaction between a challenging environment and the mental capital of individuals. Additionally, we posit that mindfulness-based practices are instrumental for the development of major components of mental capital, such as resilience, flexibility of mind, and learning skills, while also serving as a pathway to enhance empathy, compassion, self-awareness, conflict resolution, and relational abilities. Importantly, the evidence base supporting the effectiveness of mindfulness-based interventions has been increasing over the years, and a growing number of medical schools have already integrated mindfulness into their curricula. While we acknowledge that mindfulness is not a panacea for all educational and mental health problems in this field, we argue that there is currently an unprecedented opportunity to gather momentum, spread and study mindfulness-based programs in medical schools around the world as a way to address some longstanding shortcomings of the medical profession and the health and educational systems upon which it is rooted.
Keywords: Mindfulness; Medical education; Mental capital; Mental health; Medical students; Resilience